De Novo Reconstruction of 3D Human Facial Images from DNA Sequence - Mingqi Jiao; Jiarui Li; Bingxu Zhong; Siyuan Du; Shuning Li; Manfei Zhang; Qibin Zhang; Zhongming Liang; Fan Liu; Chunman Zuo; Sijia Wang; Luonan Chen (Advanced Science)
Abstract Facial morphology is a distinctive biometric marker, offering invaluable insights into personal identity, especially in forensic science. In the context of high‐throughput sequencing, the reconstruction of 3D human facial images from DNA is becoming a revolutionary approach for identifying individuals based on unknown biological specimens. Inspired by artificial intelligence techniques in text‐to‐image synthesis, it proposes Difface, a multi‐modality model designed to reconstruct 3D facial images only from DNA. Specifically, Difface first utilizes a transformer and a spiral convolution network to map high‐dimensional Single Nucleotide Polymorphisms and 3D facial images to the same low‐dimensional features, respectively, while establishing the association between both modalities in the latent features in a contrastive manner; and then incorporates a diffusion model to reconstruct facial structures from the characteristics of SNPs. Applying Difface to the Han Chinese database with 9,674 paired SNP phenotypes and 3D facial images demonstrates excellent performance in DNA‐to‐3D image alignment and reconstruction and characterizes the individual genomics. Also, including phenotype information in Difface further improves the quality of 3D reconstruction, i.e. Difface can generate 3D facial images of individuals solely from their DNA data, projecting their appearance at various future ages. This work represents pioneer research in de novo generating human facial images from individual genomics information.